2021
DOI: 10.3390/ijerph18020634
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Birth Outcomes Due to Exposure to Household Air Pollution from Unclean Cooking Fuel among Women of Reproductive Age in Nigeria

Abstract: Exposure to household air pollution (HAP) from cooking with unclean fuels and indoor smoking has become a significant contributor to global mortality and morbidity, especially in low- and middle-income countries such as Nigeria. Growing evidence suggests that exposure to HAP disproportionately affects mothers and children and can increase risks of adverse birth outcomes. We aimed to quantify the association between HAP and adverse birth outcomes of stillbirth, preterm births, and low birth weight while control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…A secondary analysis of the Nigerian Demographic and Health Survey determined the magnitude of adverse perinatal outcomes at 14.9%. 5 A systematic review and metaanalysis study in Sub-Saharan Africa reported a pooled prevalence of 29.7%. 6 Besides, the magnitude of perinatal complication was 18.2% in Butajira, 7 21% in Bale Zone, 8 and 18.3% in Hawassa town.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary analysis of the Nigerian Demographic and Health Survey determined the magnitude of adverse perinatal outcomes at 14.9%. 5 A systematic review and metaanalysis study in Sub-Saharan Africa reported a pooled prevalence of 29.7%. 6 Besides, the magnitude of perinatal complication was 18.2% in Butajira, 7 21% in Bale Zone, 8 and 18.3% in Hawassa town.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, low ambient temperature was likely linked to high levels of indoor air pollution from biofuel sources, and therefore might have increased the risk of adverse birth outcomes, as demonstrated by a number of studies in low-income settings. 38 40 However, these health effects (temperature impacts on birth outcomes mediated by indoor pollution) would occur at longer time lags than investigated in the present study.…”
Section: Discussionmentioning
confidence: 66%
“…Adverse birth outcomes (stillbirth, preterm births and low birth weight) due to exposure to household air pollution from unclean cooking fuel in Nigeria were also assessed in a study using Bayesian models, taking into account geographic variability [15]. Using data obtained in a national cross-sectional survey, unclean fuel was the primary source of cooking for 89.3% of the women and the risk of stillbirth was significantly higher for mothers using this type of cooking fuel.…”
Section: Health Impacts Of Human Exposure To Air Pollutionmentioning
confidence: 99%